Labor market integration of migrants: Hidden costs and benefits in two-tier welfare states - Jan König; Christoph Skupnik (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
We apply a monopoly trade union model and analyze employment, wage and budgetary effects of (i) an inflow of migrant workers and (ii) an increase in the labor market participation rate of migrants. Per assumption, natives and migrants solely differ with respect to the level of benefit claims in a two-tier welfare system. Furthermore, the labor effects are studied under two types of union behavior. Analyzing the ceteris paribus labor market effects, we identify hidden costs and benefits of intensified integration that emerge from the design of the welfare program. We support previous findings in case of an inflow of migrant workers. More interesting, though, it is shown that a larger share of migrants in the workforce increases (decreases) the employment level, if the union represents (does not represent) migrant workers.
Keywords: F22; H53; J15; J2; J5; J61; R23; 330; migration; welfare state; trade union; Migranten; Berufliche Integration; Sozialhilfe; Soziale Integration; Gewerkschaft; Monopol; Lohn; Beschäftigungseffekt; Bevölkerung; Theorie